2020
DOI: 10.4038/jula.v23i2.7975
|View full text |Cite
|
Sign up to set email alerts
|

Reopening the academic library in the post-pandemic season: A lesson-learned from the COVID-19 pandemic

Abstract: Information has becoming the most valuable asset in the emerging world. Hence, information has become one of the major driving forces that lead a country towards sustainable development. While the libraries and other information centers are closed around the world, it could be adversely affected on the economy and general livelihood of the society. Thus, continuing the information services uninterruptedly is a matter of significance. However, the continuum of library services during lock-down situations and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…According to the ALA, 99% of all libraries initially limited access to the physical libraries at the beginning of the pandemic. However, many libraries have also reported that they are planning to reopen on some level to meet the needs of students and researchers (Fernando and Jayasekera, 2020).…”
Section: Decline In the Usage Statistics Of The Selected University L...mentioning
confidence: 99%
“…According to the ALA, 99% of all libraries initially limited access to the physical libraries at the beginning of the pandemic. However, many libraries have also reported that they are planning to reopen on some level to meet the needs of students and researchers (Fernando and Jayasekera, 2020).…”
Section: Decline In the Usage Statistics Of The Selected University L...mentioning
confidence: 99%